The Relationship between Sleep Quality and Body Mass Index (BMI) with Excessive Daytime Sleepiness in Students - Miransya, Devara Aneila; Aziz, Ari Rahmat; Utomo, Wasisto (Journal of Education Technology Information Social Sciences and Health, 2024)
Excessive Daytime Sleepiness (EDS) in students often occurs. EDS can be influenced by several factors, including excessive BMI, poor sleep quality, lifestyle, mental health and neurological disorders. This study aims to determine the relationship between sleep quality and body mass index (BMI) with the incidence of excessive daytime sleepiness in students. This research uses a descriptive correlation method with a cross sectional approach. The research sample of 237 respondents who met the inclusion criteria used a probability sampling technique, namely stratified random sampling. The analysis used was bivariate analysis using the Chi Square and Kolmogorov-Smirnov tests. The results showed that the majority of respondents were women (90.7%), aged 19-21 years (63.3%), had poor sleep quality (87.8%), normal BMI category (62%), and the majority of respondents experienced Excessive Daytime Sleepiness EDS (71.3%). The chi-square results of the relationship between sleep quality and EDS obtained p-value = 0.937 α (0.05) and the Kolmogorov-Smirnov results of the relationship between BMI and EDS obtained p-value = 0.274 α (0.05). There is no significant relationship between sleep quality and the incidence of Excessive Daytime Sleepiness (EDS) in students and there is no relationship between body mass index and the incidence of Excessive Daytime Sleepiness (EDS). It is hoped that the results of this research can be used as suggestions for students to improve sleep quality.